Expenditures’ level and efficiency in Public Education: a Study of São Paulo Municipalities Using Data Envelopment Analysis - Matias, Alberto Borges; Quaglio, Gislaine de Miranda; Oliveira, Bruno Garcia de; Lima, João Paulo Resende de; Bertolin, Renan Vilela (Revista de Administração da UFSM, 2019)
The quality of education offered by the public sector is important for impact in the formation of the citizen and the generation of human capital. In this context, studying the level of public spending and management efficiency allows us to identify best practices, and strengthen the assessment of the public sector as a mechanism of social control and effectiveness of the state. This article aims to assess the level of municipal spending on education in relation to efficiency in the promotion of basic education quality. 47 counties, with the use of Data Envelopment Analysis (DEA) in a model using three inputs and six outputs for the years 2007, 2009 and 2011 were analyzed. The results indicate an increase in total spending on education, however, the greater allocation of resources did not provide better results, since the application was inefficient.